THE INFLUENCE OF PERCEIVED PRODUCT QUALITY, PROMOTIONAL ATTRACTIVENESS, AND BRAND AMBASSADOR ON EMINA COSMETIC PURCHASING DECISIONS WITH BRAND IMAGE AS INTERVENING VARIABLE - Vicky Brama Kumbara; Yulasmi -; Emil Salim; Ramdani Bayu Putra; Della Asmaria Putri (Jurnal Ipteks Terapan, 2023)
The purpose of this study was to analyze the effect of perceived product quality, promotional attractiveness, and brand ambassadors on purchasing decisions with brand image as an intervening variable. This research was conducted on consumers who made purchases at Emina cosmetics, where the respondents in this study were students of the Faculty of Economics and Business, Putra Indonesia University in the 2021-2022 academic year. The number of samples in this study were 131 respondents. With the method of collecting data through questionnaires and the sampling method in this study was non-probability sampling with purposive sampling technique. This study uses Partial Least Square analysis techniques estimated with the SmartPLS 2.0 program. The results of this study are the perception of product quality, promotional attractiveness, brand ambassadors and brand image as intervening variables that have a direct and indirect effect on purchasing decisions. Brand image is the factor that most influences consumers in making purchasing decisions. So that the higher the brand image of a product, the higher the consumer purchasing decision for that product. The perceived benefits greatly influence consumer purchasing decisions in making Emina cosmetic products.